Characteristics of volatile organic compounds (VOCs) based on multisite observations in Hebei province in the warm season in 2019. (1st July 2021) - Wang, Zhanshan; Wang, Haiyong; Zhang, Liang; Guo, Jian; Li, Zhigang; Wu, Kai; Zhu, Guiyan; Hou, Dongli; Su, Haiyan; Sun, Zhaobin; Wei, Yongjie; Qian, Yan
Abstract: Hebei is one of the most air-polluted provinces located in China. In this study, NOx, volatile organic compounds (VOCs), and ozone (O3 ) observational data obtained at 7 monitoring sites in Hebei Province in the warm season (May to September) in 2019 were analyzed to investigate the spatiotemporal distribution, composition characteristics, and chemical reactivity of VOCs. Results indicated that VOCs concentrations were the highest in Shijiazhuang and Langfang (47.8 and 39.2 ppb, respectively) and the lowest in Zhangjiakou and Chengde (16.6 and 12.0 ppb, respectively). In the warm season in 2019, the monthly average concentrations of VOCs increased initially and decreased subsequently, and the highest concentration found in July and August. The diurnal variation patterns of VOCs exhibited a double-peak curve, with the first peak occurring between 07:00–09:00, influenced by the production and life activities of residents. The second peak occurred between 23:00–0:00 due to the poor atmospheric diffusion conditions at nighttime and the possible transportation from residual layer. Alkanes, haloalkanes, and alkenes were responsible for the largest components to VOCs in Hebei Province, with the average proportions at the 7 monitoring sites of 43.25%, 30.39% and 15.00%, respectively. The ratios of toluene to benzene (T/B) of the monitored sites indicated that the VOCs concentrations at the Shijiazhuang and Xingtai sites were mainly influenced by emissions from coal combustion. In comparison, the VOCs concentrations at the Baoding and Langfang sites were mainly influenced by motor vehicle emissions, while the sites at Zhangjiakou and Chengde were mainly influenced by solvent-based coating and industrial process emissions. Alkenes had the highest chemical reactivity of the VOCs in Hebei Province, ethylene, propene, toluene, and 1-butene were also the high chemical reactivity species. Lastly, tailored schemes for the reduction of O3 precursor were proposed based on the NOx, VOCs, and O3 data obtained from the various monitoring sites. Highlights: VOCs concentrations were highest in Shijiazhuang and Langfang in Hebei, China. Ethylene, propene and toluene provided the greatest contributions to O3 formation. Tailored schemes for the reduction of O3 precursor were proposed.